1991
DOI: 10.1177/0272431691114001
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Interdisciplinary Teaming and its Influence on Student Self-Concept in Middle Schools

Abstract: The present study examined the degree to which interdisciplinary teaming was implemented in middle schools and the resulting impact of interdisciplinary teaming on students' self-concepts. The degree of interdisciplinary teaming was measured by means of the stages-of-concern and level-of-use instruments that are components of the Concerns-Based Adoption Model (CBAM). Student self-concept was measured by the Piers-Harris Self-Concept Scale. Results showed that the majority of teachers and administrators in Iowa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Student outcomes have also been addressed in some studies of interdisciplinary teacher teaming. These studies suggest that students at teaming schools have higher levels of social bonding with peers, teachers, and their schools (Arhar, 1990); report more satisfaction with their fellow students (Pounder, 1999); feel less anonymity and isolation (Clark & Clark, 1994); and have higher levels of self-concept (Stefanich, Wills, & Buss, 1991) than do their nonteaming student counterparts. Studies have also identified important outcomes in student achievement as a result of interdisciplinary teaming and other middle-level implementations.…”
Section: Team-related Outcomesmentioning
confidence: 99%
“…Student outcomes have also been addressed in some studies of interdisciplinary teacher teaming. These studies suggest that students at teaming schools have higher levels of social bonding with peers, teachers, and their schools (Arhar, 1990); report more satisfaction with their fellow students (Pounder, 1999); feel less anonymity and isolation (Clark & Clark, 1994); and have higher levels of self-concept (Stefanich, Wills, & Buss, 1991) than do their nonteaming student counterparts. Studies have also identified important outcomes in student achievement as a result of interdisciplinary teaming and other middle-level implementations.…”
Section: Team-related Outcomesmentioning
confidence: 99%
“…Research on middle school interdisciplinary teams also indicates favorable outcomes for students. Specifically, students at teamed schools have higher levels of social bonding with peers, teachers, and their school (Arhar, 1990), feel less anonymity and isolation (Clark & Clark, 1994, p. 125), and have higher levels of self-concept (Stefanich, Wills, & Buss, 1991) than do their nonteaming counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This belief is supported by Rosenberg (1976) who has concluded that teachers can be instrumental in the formation of young adolescents' self-concepts. Recently, Stefanich, Wills, and Buss (1991) found that "interdisciplinary teaming appears to play a role in favorably mediating the self-concepts of middle school students" (p. 404). However, what role might CPT for teachers have in this finding?…”
Section: Self-conceptmentioning
confidence: 99%